2023
DOI: 10.1007/s44174-023-00067-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bacteriostatic Properties of Ti Alloys by Surface Nitriding

Abstract: Surface nitriding has been widely used to improve the surface physicochemical properties of Ti alloys. However, the currently utilized surface nitriding methods, such as laser nitriding, typically require expensive and complicated instruments, which makes surface nitriding a less cost-effective process. Meanwhile, the antibacterial properties of surface-nitrided Ti alloy implants have not been evaluated. Thereafter, in this study, we were aiming to develop an effective, simple, and cost-effective surface nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Silicon nitride has been found to have antibacterial effects on Gram-positive and Gram-negative bacteria. A lot of in vitro studies have demonstrated the antibacterial activity of silicon nitride against different microorganisms such as Escherichia coli, Staphylococcus epidermidis, and Porphyromonas gingivalis [23,[25][26][27][28][29][30][31][32]. Silicon nitride also exhibits excellent antibacterial properties in animals [33].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride has been found to have antibacterial effects on Gram-positive and Gram-negative bacteria. A lot of in vitro studies have demonstrated the antibacterial activity of silicon nitride against different microorganisms such as Escherichia coli, Staphylococcus epidermidis, and Porphyromonas gingivalis [23,[25][26][27][28][29][30][31][32]. Silicon nitride also exhibits excellent antibacterial properties in animals [33].…”
Section: Introductionmentioning
confidence: 99%